Investigation on Wear Behavior and Chip Formation During Up-Milling and Down-Milling Operations for Inconel 718 - Kasim, Mohd Shahir (Penerbit Universiti Teknologi Malaysia, 2014)
A comprehensive study and FEM simulation of ball nose end milling on tool wear behavior and chip formation had been performed on Inconel 718 (nickle-based superalloy) under minimum quantity lubricant (MQL) condition. In this paper, the investigation was focusing on the comparison of up-milling and down-milling operations using a multi-layer TiAlN/AlCrN-coated carbide inserts. A various cutting parameters; depth of cut, feed rate and cutting speed were considered during the evaluation. The experimental results showed that down-milling operation has better results in terms of tool wear compared to up-milling operation. Chipping on cutting tool edge responsible to notch wear with prolong machining. It was observed that the chips formed in up-milling operation were segmented and continuous, meanwhile down-milling operation produced discontinuous type of chips.